Information Transfer Technique to Improve Beginner Level Students’ Listening Skill and Classroom Participation - Yuslaili Ningsih; Nanik Mariyati (Journal of English in Academic and Professional Communication, 2022)
The lack of English vocabulary makes listening the most challenging skill for most of EFL students. Some techniques have been applied to help students overcome their difficulties in learning English. This research aimed at improving non-English department students’ listening skill and engagement by using information transfer technique. The design used was classroom action research that consisted of planning, implementation, observation and reflection. The data were taken from the pre-test and post-test results. The instruments used were listening task, observation, and questionnaire. The findings showed that by using transformation transfer of reading text, the EFL students got much better listening comprehension and were more involved in their classroom activities. Thus, more techniques to improve students’ language skill should be implemented.